The Masks We Wear: False Self as a Response to Existential Isolation in No Longer Human - Malik, Momal Masood; Bashir, Saima (Pakistan Languages and Humanities Review, 2025)
This research analyses Yozo Oba, the protagonist of Osamu Dazai’s No Longer Human (1958) and his existential dilemma of isolation alongside his need to belong. Such a conflict creates anxiety, leading to fabricated personas, and the study investigates its sociological impacts as well as Yozo’s lack of resolution. Through the application and integration of Irvin Yalom’s existential isolation and Donald Winnicott’s false self, the study interprets Yozo as ultimately hiding behind the mask of this false self and failing to realise his truth. The research employs close reading and qualitative analysis of the text to reveal that in a world littered with elaborate facades and social pressures, to be human is to embrace one’s truth, cast off one’s mask and navigate the delicate balance between isolation and Additional research is required to explore the relationship between existential isolation and the false self and its representation within the literary domain.